ANALISIS PERMINTAAN DAGING AYAM DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA DENGAN MENGGUNAKAN MODEL REGRESI TERSENSOR - Nguyen Khac Hoen; Slamet Hartono; Ma Soedjono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1999)
The chicken is a relative popular food in Indonesia in general and in Yogyakarta Special Region in particular. Demand for the chicken.